Geomorphic response of the rivers Tulin and Turrubaritos to the deformation associated with the angostura fault, a Central Forearc in Costa Rica. - Porras-Espinoza, Hernán; Fallas-Salazar, Carolina; Stanlyn Sarmiento, Kevin; Arroyo-Solorzano, Mario (Revista Geográfica de América Central., 2018)
The Angostura fault, located in the central outer forearc of Costa Rica, is a normal fault that presents a relay system using a ramp. This fault, implanted within the basement associated with the Tulin Formation, was active during the Early Miocene, thus generating a series of depocenters within which sediments of the Formación Punta Carballo would have been deposited. The geomorphic indices, as well as the analysis of the pattern of drainage and the paleochannels, suggest that this fault has actively contributed in the modeling of the landscape; however, it does not present activity since, at least, the Middle Miocene to the present.